État(s) des lieux : espaces et topographies dans la collection Gaignières - Damien Bril (Les Cahiers de l'École du Louvre)
This article looks at the recent development of work devoted to the topographical dimensions of the Gaignières collection. With the introduction of the Collecta database, it is now possible to take an overview of the collection’s approach, to measure more clearly the links between the major series that make up and organise the collection, and to understand that the views of monuments that had previously been extracted from the collection as traces of buildings or tombs that had disappeared, were part of and took their value from an overall project, of which they were the sole emanation. To do so, we will first recall the nature of Gaignières’ project and the role played by topographical data in structuring his collection ; then we will look at the scientific and methodological means used to achieve it ; and, finally, we will examine the practices surrounding the constitution of the collection, and the questions that they may raise for the contemporary historian.